2019
DOI: 10.1371/journal.pone.0218369
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the performance and clinical utility of point of care HIV-1 RNA testing for diagnosis and care

Abstract: Background Point of-care (POC) HIV-1 RNA tests which are accurate and easy to use with limited infrastructure are needed in resource-limited settings (RLS). We systematically reviewed evidence of POC test performance compared to laboratory-based HIV-1 RNA assays and the potential utility of these tests for diagnosis and care in RLS. Methods Studies published up to July 2018 were identified by a search of PUBMED, EMBASE, Web of Science, CINAHL and Cochrane Central Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…In the studies included in this review, on‐site AEHI diagnosis was not possible in community‐based testing settings, but required laboratory‐based tests and skilled laboratory personnel. The emergence of point‐of‐care HIV‐RNA tests may enable on‐site community‐based AEHI testing in SSA [21]. However, no study approached AEHI testing in a comprehensive, culturally sensitive and integrated fashion in SSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies included in this review, on‐site AEHI diagnosis was not possible in community‐based testing settings, but required laboratory‐based tests and skilled laboratory personnel. The emergence of point‐of‐care HIV‐RNA tests may enable on‐site community‐based AEHI testing in SSA [21]. However, no study approached AEHI testing in a comprehensive, culturally sensitive and integrated fashion in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, diagnosis of EHI requires a combination of HIV antibody, HIV‐RNA, and/or p24 assays [8,18‐20]. While AEHI testing, here defined as testing with a combination of HIV antibody, HIV‐RNA and p24 assays, was not available in most of SSA until recently, the emergence of point‐of‐care HIV‐RNA testing in SSA enables AEHI testing among a range of populations [21]. In some well‐resourced countries, national guidelines recommend AEHI testing for people who report risk behaviour and symptoms associated with AEHI [22,23], and facility‐based AEHI testing with HIV‐RNA can successfully identify AEHI among MSM [16,24‐29].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found POC technologies to have high diagnostic accuracy [30,31] and be cost effective compared to conventional laboratory-based testing [1620]. How these technologies perform in low throughput settings, what the strategies for scale-up of POC technologies are and whether they remain cost-effective relative to conventional centralized laboratory testing in terms of diagnostic accuracy or clinical impact, however, is not well understood [22,30]. By optimizing the allocation of POC technologies to reach the ‘last mile’ of viral load volumes, we have shown that costs can be reduced by as much as 35% for these viral loads compared to integrating these facilities into the centralized laboratory system, despite the cost of POC equipment and low patient volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Detection and management of AHI has been called a “clinical and public health emergency” [ 14 ] and a “common occurrence overlooked” [ 35 ]. POC HIV-1 RNA testing is becoming more available in sub-Saharan Africa and has multiple clinical uses, including viral load monitoring, early infant diagnosis, and AHI detection [ 36 ]. Because the cost of HIV-1 RNA testing is considerable, detection of AHI in resource-limited countries should be targeted using algorithms that identify at-risk individuals [ 37 ].…”
Section: Discussionmentioning
confidence: 99%